The combined effects of halo and linear doping effects on the high-frequency and switching performance in ballistic CNTFETs - 王伟 张露 王雪莹 王竹兵 张婷 李娜 杨晓 岳工舒 (Journal of semiconductors, 2014)
To overcome short-channel effects （SCEs） in high-performance device applications, a novel structure of CNTFET with a combination of halo and linear doping structure （HL-CNTFET） has been proposed. It has been theoretically investigated by a quantum kinetic model, which is based on two-dimensional non-equilibrium Green＇s functions solved self-consistently with Poisson＇s equations. We have studied the effect of halo doping and linear doping structure on static and dynamical performances of HL-CNTFET. It is demonstrated that a halo doping structure can decrease the drain leakage current and improve the on/off current ratio, and that linear doping can improve high-frequency and switching performance.